2020
DOI: 10.3390/ijerph17155442
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Program to Strengthen Self-Reflection and Critical Thinking in Freshmen Nursing Students during COVID-19: A Quasi-Experimental Study

Abstract: This article focuses on the unique needs and concerns of nursing educators and nursing students in the face of the COVID-19 pandemic. During social distancing, interacting with other human beings has been restricted. This would undermine the experiential learning of nursing students. Hence, it is important to develop and evaluate an experiential learning program (ELP) for nursing education. A pre-test and post-test design were used. The study was conducted in a university in Central Taiwan. A total of 103 nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
2
30
0
3
Order By: Relevance
“…1. Seventeen articles published during 2004-2020 were included: including five quasi-experimental studies, three descriptive studies, four mixed method studies, and five qualitative studies [11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The total number of participants was 1,866, ranging from 14 to 613 in each study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Seventeen articles published during 2004-2020 were included: including five quasi-experimental studies, three descriptive studies, four mixed method studies, and five qualitative studies [11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The total number of participants was 1,866, ranging from 14 to 613 in each study.…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies, community-based education improved communication skills with educators, patients, community members, children, adolescents, the elderly, people with disabilities, family, patient relatives, and other health professionals [11, 12, 19, 20, 25-27, 29, 33]. Nine studies mentioned increasing self-confidence [11,20,21,23,24,[26][27][28]32] and five studies mentioned increasing knowledge and awareness [20-22, 25, 28]. Promoting teamwork skills was mentioned in four studies [25,27,29,30] and improving thinking skills through education was mentioned in three studies [11,23,25].…”
Section: Effect Of Community-based Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, their mutual understanding and effective collaboration in the administration of rural CBME can drive the smooth adaptation of the education system in this pandemic [ 35 ]. Furthermore, continuing on-site learning through an experiential learning program during the pandemic can improve medical students’ motivation and reflection on clinical medicine [ 36 ]. Based on the previous articles, medical students who are motivated to learn in rural areas can work in rural medical institutions [ 37 , 38 ], but the quality of rural CBME is critical for medical students’ motivation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the learning components including constructivism, inquiry, questioning, community learning, modelling, reflection, and authentic Work-based learning applies the principles of experiential learning. If students get direct experience to gain knowledge through learning, through cooperation, reflection, questioning, and action, they will find it easier to apply the knowledge gained and increase their ability to reflect and think critically [41]. To increase the consistency and quality of work-based learning, educational institutions can make curriculum changes and innovate in conducting learning and evaluation [42].…”
Section: Discussionmentioning
confidence: 99%